Review of exchange-rate theories in four leading economics textbooks - Jan Priewe (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2017)
In this paper, the parts of four leading economics textbooks that deal with exchange-rate theories are reviewed. The books are by Krugman/Obstfeld/Melitz, Blanchard/Johnson, Mankiw/Taylor and Samuelson/Nordhaus. The theoretical background for this exercise is the fact that exchange-rate theory is one of the weakest parts in 'mainstream economics', meaning the neoclassical and the New Keynesian stream of thought. It is now widely accepted that exchange-rate forecasts are no better than those arising from a random walk in the short and medium run. For the long run, most authors stick to the old purchasing-power-parity theory whose empirical validation is just as weak. Nonetheless the textbooks reviewed here only present exchange-rate theories that have little empirical support. Yet they differ considerably, even though they remain within the leading theoretical paradigm.
Keywords: A22; A23; F31; F41; 330; teaching economics; open-economy macroeconomics; exchange-rate theory